2013
DOI: 10.1186/1478-811x-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 mediates NF-κB signalling activation induced by high glucose in GMCs: involvement of c-Src

Abstract: BackgroundNuclear factor kappa-B (NF-κB) signalling plays an important role in diabetic nephropathy. Altered expression of connexin43 (Cx43) has been found in kidneys of diabetic animals. The aim of the current study was to investigate the role of Cx43 in the activation of NF-κB induced by high glucose in glomerular mesangial cells (GMCs) and to determine whether c-Src is involved in this process.ResultsWe found that downregulation of Cx43 expression induced by high glucose activated NF-κB in GMCs. Orverexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Thus, upregulated CCL2 could play a role in the increased severity of BBB/BSCB disruption in Cx47KO mice. Interestingly, astrocytic CCL2 expression is controlled by NF‐κB (Giraud, Caron, Pham‐Dinh, Kitabgi, & Nicot, ) and by activation of stat1 (Wang et al, ), while Cx43, the major partner of Cx47 at O:A GJs (Orthmann‐Murphy et al, ), mediates NF‐κB signaling activation (Xie et al, ). Thus, loss of Cx47 and the potential dysfunction of Cx43 (Markoullis, Sargiannidou, Gardner, et al, ) may directly affect the regulation of the astrocyte activation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, upregulated CCL2 could play a role in the increased severity of BBB/BSCB disruption in Cx47KO mice. Interestingly, astrocytic CCL2 expression is controlled by NF‐κB (Giraud, Caron, Pham‐Dinh, Kitabgi, & Nicot, ) and by activation of stat1 (Wang et al, ), while Cx43, the major partner of Cx47 at O:A GJs (Orthmann‐Murphy et al, ), mediates NF‐κB signaling activation (Xie et al, ). Thus, loss of Cx47 and the potential dysfunction of Cx43 (Markoullis, Sargiannidou, Gardner, et al, ) may directly affect the regulation of the astrocyte activation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…There was a strong trend (p=0.06) for RG but not CP diminishing the AUC for IkBa degradation. Since cytokine-induced c-Src levels might be higher in Cx43 deficient cells and since c-Src binds and thereby acts as a sink for IkBa (33, 34), we investigated c-Src expression in INS-1 cells exposed to cytokines in the presence or absence of RG or CP. As shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Cx43 down-regulation may contribute to the dysfunction of the blood-retina barrier through vascular permeability in diabetic retinopathy. Though this effect is best characterized in retinal tissue, several studies have demonstrated a significant role for Cx43 in regulation of TJ proteins, such as occludin, at the BBB (Chronopoulos et al, 2010), and ZO-1 in kidney (Xie et al, 2013). …”
Section: Pericyte Dysfunctionmentioning
confidence: 99%